Hubungan Asupan Energi, Asupan Protein Dan Status Gizi Dengan Produktivitas Kerja Pada Tenaga Kerja Wanita Bagian Finishing 3 Pt Hanil Indonesia Nepen Teras Boyolali - Astuti, Puji; , Susi Dyah Puspowati, SP., M.Si (2017)
Background: Labor productivity is a measure of the success of the workers producing a product in a certain time unit (Hafner et, al., 2007). Food consumption and nutritional status of workers considered quite important in improving the productivity of labor. Disadvantages of energy and protein intake cause low energy production so that the body will be weakened as immune system, physical labor activity, and thinking power. Workers with abnormal nutritional status would work slowly and inactive so the productivity of work decreases. Purpose : Purpose research is determine rrelation between energy intake, protein intake and nutritional status with work productivity of the female workers in section Finishing 3 PT. Hanil Indonesia NepenTeras Boyolali. Methods : The research cross sectional design study with ervational study. Total sample is 45 people. The sampling technique using simple random sampling. Data of energy and protein intake using food recall 24 hours, nutritional status by measuring weight and height, and labor productivity was obtained sheet observation weighing yarn. Statistical analysis using Spearmean Rank test. Results : The survey results that 53.3% of respondents have less energy intake, 64.4% had less protein intake, 44.4% had a normal utritional status and 68,9% have a high work productivity. The results of bivariat test, correlation for protein intake with labor productivity value of p =0.988; correlation for energy ntake with labor productivity value of p ,048,correlationnutritional status with labor productivity value of p =0.005. Conclusion : Nothing correlation for protein intake with labor productivity. There is a correlation energy intake, nutritional status with labor productivity of female workers in section Finishing 3 PT. Hanil Indonesia Nepen Teras Boyolali. Key Words : energy intake, female workers, labor productivity, nutritional status, protein intake.